Genome-Wide Identification, Transcript Profiling and Bioinformatic Analyses of GRAS Transcription Factor Genes in Rice - Dutta, Mouboni; Saha, Anusree; Moin, Mazahar; Kirti, Pulugurtha Bharadwaja (Frontiers in Plant Science, 2021)
Our group has previously identified the activation of a GRAS transcription factor (TF) gene in the gain-of-function mutant population developed through activation tagging in rice (in an indica rice variety, BPT 5204) that was screened for water use efficiency. This family of GRAS transcription factors has been well known for their diverse roles in gibberellin signaling, light responses, root development, gametogenesis etc. Recent studies indicated their role in biotic and abiotic responses as well. Although this family of TFs received significant attention, not many genes were identified specifically for their roles in mediating stress tolerance in rice. Only OsGRAS23 (here named as OsGRAS22) was reported to code for a TF that induced drought tolerance in rice. In the present study, we have analyzed the expression patterns of rice GRAS TF genes under abiotic (NaCl and ABA treatments) and biotic (leaf samples infected with pathogens, Xanthomonas oryzae pv. oryzae that causes bacterial leaf blight and Rhizoctonia solani that causes sheath blight) stress conditions. In addition, their expression patterns were also analyzed in thirteen different developmental stages. We studied their spatio-temporal regulation and correlated them with the in-silico studies. Fully annotated genomic sequences available in rice database have enabled us to study the protein properties, ligand interactions, domain analysis and presence of cis-regulatory elements through the bioinformatic approach. Most of the genes were induced immediately after the onset of stress particularly in the roots of ABA treated plants. OsGRAS39 was found to be a highly expressive gene under sheath blight infection and both abiotic stress treatments while OsGRAS8, OsSHR1 and OsSLR1 were also responsive. Our earlier activation tagging based functional characterization followed by the genome-wide characterization of the GRAS gene family members in the present study clearly show that they are highly appropriate candidate genes for manipulating stress tolerance in rice and other crop plants.